Updating Conductivity Tensor of Cold and Warm Plasma for Equatorial Ionosphere F2-Region in The Northern Hemisphere - Yesil, Ali; Sagir, Selcuk (Springer International Publishing Ag, 2019)
We compared the conductivity tensor becoming important parameter of ionospheric plasma using the real geometry of Earth's magnetic field in the Northern hemisphere for both cold and warm ionospheric plasma for equinox days. It could be that the conductivity tensor certainly depends on the vector of wave propagation (k) and the adiabatic sound speed (U (e)) in warm ionospheric plasma and it is possible to say that the adiabatic sound speed for electron generally decreases the magnitudes of conductivity tensor components with respect to the cold ionosphere plasma except for (U (e) not equal 0) = (U (e) = 0), (U (e) not equal 0) = (U (e) = 0), (U (e) not equal 0) = (U (e) = 0) and (U (e) not equal 0) = (U (e) = 0). In this sense, the resistivity and reactance increase in ionospheric plasma. In this context, according to the accepted conditions, the change of conductivity with local time is similar to change of electron density with local time for both (cold and warm) conditions in ionospheric plasma as trend.
Keywords: The adiabatic sound speed; Conductivity tensor; Ionospheric F2 layer; Cold and warm plasma